Genetic Variability in Growth Characteristics among Different Clones of Eucalyptus tereticornis Sm. - Sahoo, Hareram; Lenka, Devraj; Mohanty, T. L.; Mishra, P.; Mishra, Yogeshwar; Kumar, Aditya (International Journal of Bio-resource and Stress Management, 2021)
The present investigation was carried out at the College of Forestry, Odisha University of Agriculture and Technology, Bhubaneswar, Odisha, India during August, 2018 to June, 2019 to study the genetic variability in growth characteristics among different clones of Eucalyptus tereticornis. Different clones of Eucalyptus tereticornis Sm. were planted in RCBD, with 4 replications revealed significant variations among all eight treatments (clones) with respect to 9 different characters. Based on the mean performance, treatment-1 (clone-526) showed maximum value for characters like biomass (1124.17), plant height (247.9 cm), collar diameter (23.25 mm), and a number of leaves plant-1 (463.25 number). Similarly, the maximum value was observed in treatment-8 (clone-136) for traits like leaf area (42.70 cm2), leaf length (15 cm), and leaf width (5.75 cm). The highest leaf length to leaf width ratio (3.57) and lowest number of branches plant-1 (18.75 number) were found in treatment-2 (clone-288). All characters had exhibited higher genotypic variance than an environmental variance. Similarly, the genetic coefficient of variation in the case of all variables was also found greater than an environmental coefficient of variation. Heritability was found maximum in plant height (87.35%) and all other characters also showed high heritability. Genetic advance as % of mean was found maximum in biomass (71.15%). Based on the overall mean performance of growth characters, Treatment-1 (Clone-526) was found as a superior clone with respect to the most important character biomass for the test locality. High GCV, heritability, and GAM value for biomass indicated that the character would respond to selection for the improvement program.